Long-Term Exposure of Early-Transformed Human Mammary Cells to Low Doses of Benzo[a]pyrene and/or Bisphenol A Enhances Their Cancerous Phenotype via an AhR/GPR30 Interplay - Donini, Caterina F.; El Helou, Myriam; Wierinckx, Anne; Győrffy, Balázs; Aires, Sophie; Escande, Aurélie; Croze, Séverine; Clezardin, Philippe; Lachuer, Joël; Diab-Assaf, Mona; Ghayad, Sandra E.; Fervers, Béatrice; et al. (Frontiers in Oncology, 2020)
It is of utmost importance to decipher the role of chronic exposure to low-doses of environmental carcinogens on breast tumor progression. The early-transformed triple-negative human mammary MCF10AT1 cells were chronically (60 days) exposed to low doses (10-10 M) of Benzo[a]pyrene (B[a]P), a genotoxic agent, and/or Bisphenol A (BPA), an endocrine disruptor. Our study revealed that exposed MCF10AT1 cells developed, in a time-dependent manner, an acquired phenotype characterized by an increase in cancerous properties (anchorage independent growth and stem-like phenotype). Co-exposure of MCF10AT1 cells to B[a]P and BPA led to a significantly greater aggressive phenotype compared to B[a]P or BPA alone. This study provided new insights into the existence of a functional interplay between the aryl hydrocarbon receptor (AhR) and the G protein-coupled receptor 30 (GPR30) by which chronic and low-dose exposure of B[a]P and/or BPA fosters the progression of MCF10AT1 cells into a more aggressive substage. Experiments using AhR or GPR30 antagonists, siRNA strategies and RNAseq analysis led us to propose a model in which AhR signaling plays a “driver role” in the AhR/GPR30 cross-talk in mediating long-term and low dose exposure of B[a]P and/or BPA. Retrospective analysis of two independent breast cancer cohorts revealed that the AhR/GPR30 mRNA expression signature resulted in poor breast cancer prognosis, in particular in the ER-negative and the triple-negative subtypes. Altogether, our results indicate that the engagement of both AhR and GPR30 functions, in particular in an ER-negative/triple negative context of breast cells, favors tumor progression and leads to poor prognosis. Future strategies targeting both AhR and GPR30 may thus lead to the development of new preventive strategies capable of blocking mammary carcinogenesis linked with chronic exposure to B[a]P and/or BPA environmental pollutants.